2021
DOI: 10.13057/biodiv/d220541
|View full text |Cite
|
Sign up to set email alerts
|

Pests and diseases on Falcataria moluccana trees in agroforestry systems with pineapple in East Java, Indonesia

Abstract: Abstract. Rahayu S, Triyogo A, Widyastuti SM, Musyafa’, Ardianyah F. 2021. Pests and diseases on Falcataria moluccana trees in agroforestry systems with pineapple in East Java, Indonesia. Biodiversitas 22: 2779-2788. The agroforestry system using Falcataria moluccana (Sengon) and Ananas comosus (pineapple) is considered as a profitable intercropping system in Indonesia. To make it viable, it is necessary to evaluate the effect of mixed cropping on the incidence and severity of diseases and pests on Sengon tree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 11 publications
(14 reference statements)
0
4
0
Order By: Relevance
“…Roots play an important role in nutrient and water absorptions which will be distributed to all plant parts, resulting in a good photosynthesis process and other metabolisms (Wijayanto and Hidayanthi 2012). Besides increasing growth, the agroforestry system also becomes a way to suppress pest and disease developments (Rahayu et al 2021). In the studied area, damaged sengon caused by disease and pest was low, and there were only found damaged branch or tip death caused by weather.…”
Section: Effects Of Sengon Types and Spacing On Canopy Areamentioning
confidence: 99%
See 1 more Smart Citation
“…Roots play an important role in nutrient and water absorptions which will be distributed to all plant parts, resulting in a good photosynthesis process and other metabolisms (Wijayanto and Hidayanthi 2012). Besides increasing growth, the agroforestry system also becomes a way to suppress pest and disease developments (Rahayu et al 2021). In the studied area, damaged sengon caused by disease and pest was low, and there were only found damaged branch or tip death caused by weather.…”
Section: Effects Of Sengon Types and Spacing On Canopy Areamentioning
confidence: 99%
“…Along with the increased organic carbon content, the soil C/N ratio and organic materials in the agroforestry land can promote plant growth (Utomo et al 2016). The intercropping system in agroforestry can also reduce the spread of pests and diseases (Lestari et al 2013;Rahayu et al 2021) compared to the monoculture system (Darwiati and Anggraeni 2018;Nugroho et al 2021). From a socioeconomic view, the agroforestry system is a win-win option that can become an income source for the community (Premono and Lestari 2018;Pachas et al 2019) without changing the field tradition (huma) (Iskandar et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…(swollen stem, frass, broken top crown, fork stem), stem form, and diameter (DBH) for Clone 170 and ID_063. The information obtained in the survey activities is the incidence of damage (Rahayu et al 2021), accumulated damage of each clone of E. pellita, and grouping of compartments by damage category. and block 6 (111 0 46' 12.548'' -2 0 7' 24.284'…”
Section: Procedures Zeuzera Spp Damage Surveymentioning
confidence: 99%
“…Studying of pests' diversity, population and infestation on plants cultivation is important in pests control management to increase plants growth and yield. The Study of pests such as insects and fungus on sengon has been reported more during this time such as gall rust disease (Uromycladium falcatarium [16], Xystrocera festiva [17], Aspergillus niger [18] Eurema blanda, and Schistocerca pallens [19]. However, the study of mistletoes diversity, infestation and severity on sengon has not been reported, especially in Malang Regency East Java even in Java.…”
Section: Introductionmentioning
confidence: 99%